Analisis Perekonomian Empat Sektor : Dampak Ekspor Dan Impor Terhadap Pertumbuhan Ekonomi Di Sumatera Utara Melalui Uji Regresi Linear Berganda Periode 2001-2021 - Maya Wulandari; Sarah Bakara; Alawi Parlindungan Hasibuan; Fitrawaty (CV. Ulil Albab Corp, 2024)
This study aims to analyze the influence of exports and imports on the rate of economic growth in North Sumatra, both separately and simultaneously. The method used in this study is descriptive by utilizing secondary data obtained from the Central Statistics Agency of North Sumatra Province. The data analyzed is a time series from 2001 to 2021, covering economic growth, exports, and imports. Data collection was carried out through time series and literature studies with a quantitative approach. The analysis was carried out using multiple linear regression with the help of the SPSS program. The results show that partially, exports and imports do not have a significant influence on economic growth, and simultaneously, both also do not have a significant effect on economic growth in North Sumatra.